KKN UNEJ Berkolaborasi dengan Kader Digital Optimalkan Pelayanan Desa Condro dengan Pendampingan Management Media Sosial - Enensi Lady Firdaus; Nur Akidahtul Jannah; Sigit Prastowo (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Along with the development of information technology, many villages in Indonesia have implemented smart villages, one of which is Condro Village in Lumajang Regency. However, the implementation experienced several obstacles, the first is the lack of society knowledge about digital literacy and the second is the difficulty of informing the society that village services can be accessed online. Therefore, this program aims to develop management several Condro’s social media and also disseminating information to villagers effectively. There are 3 methods used in this article. Such as planning, implementation and evaluation. The result of the application of these 3 methods is by conducting socialization, training, and mentoring of village digital cadres. Thus, synergy based on the utilization of information technology will be able to improve the quality of village social media and information dissemination to the society.